2017
DOI: 10.1038/ngeo2882
|View full text |Cite
|
Sign up to set email alerts
|

Historical carbon dioxide emissions caused by land-use changes are possibly larger than assumed

Abstract: The terrestrial biosphere absorbs about 20% of fossil-fuel CO2 emissions. The overall magnitude of this sink is constrained by the difference between emissions, the rate of increase in atmospheric CO2 concentrations, and the ocean sink. However, the land sink is actually composed of two largely counteracting fluxes that are poorly quantified: fluxes from land-use change and CO2 uptake by terrestrial ecosystems. Dynamic global vegetation model simulations suggest that CO2 emissions from land-use change have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
291
3
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 349 publications
(304 citation statements)
references
References 68 publications
(31 reference statements)
7
291
3
3
Order By: Relevance
“…In the ORCHIDEE model, increasing CO 2 leads to a fertilization effect as it increases the NPP and results in an increase in biomass production on land for most PFTs, depending on the temperature and moisture conditions (Arneth et al, 2017;Piao et al, 2009). Figure 9 shows the contribution of this fertilization effect to the cumulative SOC stock change during 1850-2005 (S4-S8), which is in the same order of magnitude as the effect of LUC excluding soil erosion.…”
Section: Effects Of Atmospheric Co 2 Increasementioning
confidence: 61%
“…In the ORCHIDEE model, increasing CO 2 leads to a fertilization effect as it increases the NPP and results in an increase in biomass production on land for most PFTs, depending on the temperature and moisture conditions (Arneth et al, 2017;Piao et al, 2009). Figure 9 shows the contribution of this fertilization effect to the cumulative SOC stock change during 1850-2005 (S4-S8), which is in the same order of magnitude as the effect of LUC excluding soil erosion.…”
Section: Effects Of Atmospheric Co 2 Increasementioning
confidence: 61%
“…In a recent review (Prestele et al, 2017), proper representation of gross LUC or sub-grid bidirectional land turnover has been identified as one of the three major challenges in implementing LUC in DGVMs for credible climate assessments, despite that these have already been pioneered by some models (Table 1). Large underestimation of LUC emissions would occur when gross LUC is ignored, as is shown by several model results reviewed in Arneth et al (2017).…”
Section: Discussionmentioning
confidence: 99%
“…All models in Table 1 include shifting cultivation and wood harvest except that shifting cultivation is not included in ISAM, and five of them include sub-grid secondary land tiles when accounting for LUC. A recent review by Arneth et al (2017) found that including processes that have been previously neglected in DGVMs, including gross transitions and other land management processes such as crop harvest and management, can lead to an upward shift of estimated LUC emissions. Their study thus highlights the importance of including these processes.…”
mentioning
confidence: 99%
“…Arneth et al (2017) reviewed the "missing processes" in LULCC modelling with DGVMs and found that ignoring gross LULCC could underestimate the global E LULCC by 36 Pg C on average over the historical period . In this study, we used a bookkeeping method to quantify the difference in LULCC emissions calculated using net versus gross forest area transitions and to show the existence of critical ratios of gross to net forest area changes above which land-use action will cause a reversed sign of cumulative carbon flux.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the non-symmetrical dynamics of CO 2 fluxes between forest loss and gain, E LULCC differs between net and gross area changes. Arneth et al (2017) recently reviewed this issue using DGVMs and concluded that considering gross LULCC significantly increased the simulated E LULCC on a global scale. Gross land-use and land-cover area transition datasets including, for example, shifting cultivation practice (Hurtt et al, 2011) and reconstructions using empirical ratios between gross and net transitions (Fuchs et al, 2015) are now available and have been implemented in a bookkeeping model (Hansis et al, 2015) as well as in some DGVMs to improve the estimate of E LULCC (Fuchs et al, 2016;Shevliakova et al, 2009;Stocker et al, 2014;Wilkenskjeld et al, 2014;Yue et al, 2017).…”
Section: Introductionmentioning
confidence: 99%